Recent advances in targeted delivery of tissue plasminogen activator for enhanced thrombolysis in ischaemic stroke. (7th February 2018) - Zamanlu, Masumeh; Farhoudi, Mehdi; Eskandani, Morteza; Mahmoudi, Javad; Barar, Jaleh; Rafi, Mohammad; Omidi, Yadollah
Abstract: Tissue plasminogen activator (tPA) is the only FDA approved medical treatment for the ischaemic stroke. However, it associates with some inevitable limitations, including: short therapeutic window, extremely short half-life and low penetration in large clots. Systemic administration may lead to complications such as haemorrhagic conversion in the brain and relapse in the form of re-occlusion. Furthermore, ultrasound has been utilised in combination with contrast agents, echogenic liposome, microspheres or nanoparticles (NPs) carrying tPA for improving thrombolysis – an approach that has resulted in slight improvement of tPA delivery and facilitated thrombolysis. Most of these delivery systems are able to extend the circulating half-life and clot penetration of tPA. Various technologies employed for ameliorated thrombolytic therapy are in different phases, some are in final steps for clinical applications while some others are under investigations for their safety and efficacy in human cases. Here, recent progresses on the thrombolytic therapy using novel nano- and micro-systems incorporating tPA are articulated. Of these, liposomes and microspheres, polymeric NPs and magnetic nanoparticles (MNPs) are discussed. Key technologies implemented for efficient delivery of tPA and advanced thrombolytic therapy and their advantages/disadvantages are further expressed.